Thirtieth Meeting of the National Development Council December 8 and 9 1973 Summary Record - Planning Commission (Planning Commission, 1973)
The problem of additional resource mobilisation by States has to be viewed in. the context of the immediate economic situation as well as in the long-term perspective regarding our social and economic objectives during the Fifth Plan. Without doubt, the immediate economic priority before the country is to stabilise the level of prices. To this end, the Government have taken a number of measures to control the level of aggregate demand by controlling the level of budget deficits and credit expansion in the private sector.
Government of India Planning Commission
Government of India Planning Commission